Integration of Islamic Values and Local Culture in the Architectural Ornaments of Old Mosques in Palu and Donggala : Integrasi Nilai Islam dan Budaya Lokal pada Ornamen Arsitektur Masjid Tua di Palu dan Donggala - Munarsi; Malik, Sutrati Melissa; Luthfiah; Irfandi; Syahrullah, Moh Rachmat (Jurnal Kolaboratif Sains, 2025)
Mosques serve as centers of worship, social interaction, education, and culture for Muslims in Indonesia. Although much research has been conducted on old mosques, studies in Palu, Sigi, and Donggala remain scarce. This study aims to explore the symbolic meaning of the ornaments of old mosques in Palu and Donggala in order to enrich the identity of Islamic architecture in the archipelago and support the preservation of cultural heritage. Using a descriptive-qualitative approach through case studies and comparisons, the analysis was conducted on five mosques: the Baiturrahim Lolu Grand Mosque, the Donggala Grand Mosque, the Auliya Towale Mosque, the Jami Kampung Baru Mosque, and the Al Amin Wani Mosque. The results show that: The Baiturrahim Lolu Mosque combines modern and local traditional styles through circular calligraphy, geometric patterns, and vegetative motifs; Masjid Raya Donggala features fluted columns, arched openings, flat domes, vine decorations, and medallion calligraphy; Masjid Auliya Towale features hexagonal and semicircular ventilation with minimal calligraphy/vegetation; The Kampung Baru Jami Mosque features gold calligraphy, geometric ventilation, star and leaf motifs in wood carvings resulting from the acculturation of Bugis, Javanese, and Chinese cultures; The Al Amin Wani Mosque is Malay-Chinese in style with Chinese minarets, ironwood pillars, calligraphy by KH Ali Yafie, and colorful vegetative ornaments on the ceiling. Analysis shows that calligraphy reinforces spirituality, geometry symbolizes cosmic order, and vegetative motifs represent closeness to nature. These findings confirm that the ornamentation of the old Pasigala mosque combines Islamic values and local traditions, highlighting the importance of preserving religious architecture as a cultural identity.